THE DEGREE OF RATIONALIZATION OF ENERGY CONSUMPTION CONCEPTS INCLUDED IN THE SCIENCE TEXTBOOKS OF THE BASIC STAGE IN JORDAN AND THE STUDENTS’ ATTITUDES TOWARDS THEM - Ahmed Qarareh; Yusef Kabbas (European Scientific Journal, ESJ, 2015)
Research aimed at identifying the degree of the rationalization of energy consumption concepts included in the sciences textbooks of the basic grades (5-8) and their attitudes towards them. To achieve the objective of the research, the researchers developed the instruments included the instrument for the analysis of the sciences textbooks, and the instrument for measuring the students` attitudes towards energy saving. Validity and reliability of the two instruments were ensured, the instrument for measuring the attitudes was applied to the sample of the study of (272) male and female students in the eighth basic grade in Tafila education directorate, T-test frequencies, and percentages were used for analyzing the independent samples. The findings indicated that the analyzed sciences textbooks included most of the concepts of the analysis instrument, but the distribution of the concepts in the content of the textbooks were at different rates, The findings of the study showed there was a shortage of the concepts include in the sciences textbooks. The results of the study also indicated that the students` attitudes towards energy saving were positive with a high degree, The findings also indicated that there were no statistical differences at level of (α = 0.05) students' attitudes towards energy saving attributed to gender, The researches recommended that the sciences textbooks should include all energy rationalization concepts and should be regular and balanced.